Correction: Boronate affinity-based photoactivatable magnetic nanoparticles for the oriented and irreversible conjugation of Fc-fused lectins and antibodies. Issue 13 (10th March 2022) - Fan, Chen-Yo; Huo, Yi-Ren; Adak, Avijit K.; Waniwan, Juanilita T.; dela Rosa, Mira Anne C.; Low, Penk Yeir; Angata, Takashi; Hwang, Kuo-Chu; Chen, Yu-Ju; Lin, Chun-Cheng
Abstract : Correction for 'Boronate affinity-based photoactivatable magnetic nanoparticles for the oriented and irreversible conjugation of Fc-fused lectins and antibodies' by Chen-Yo Fan et al., Chem. Sci., 2019, 10, 8600–8609, DOI: ; 10.1039/c9sc01613a .